Comparative tests of injectors - Newland, Ross N. (My University, 1906)
Introduction: An injector is an instrument by means of which a jet of steam acting on a jet of water with which it mingles and by which it is condensed can impart to the resulting jet of water a velocity sufficient to overcome a pressure equal to or greater than the initial pressure of the steam. The ability of the injector to force water against a pressure equal to that of the working steam makes it a very valuable instrument for supplying a boiler with feed-water. The essential difference between the injector and the other forms of jet pump is that a great part of its energy is derived from the condensation of the steam by the water. The jet pump works on the principle that when a small volume of a fluid moving at a high velocity mingles with a larger volume it can move the whole volume at a low velocity. This principle enters into the working of the injector for a small amount of steam issuing from a boiler at a high velocity will impart to a large volume of water a considerable velocity but this only a small part of the energy developed in the injector. The greater part of the energy, as has already been stated, comes from the heat contained in the steam. On the condensation of the steam this heat is given up and is converted into mechanical energy.
Citation: Newland, Ross N. Comparative tests of injectors. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Mechanical Engineering; Injectors; Boilers; Theses; Manuscripts (documents)